Sorevnovanija v detsko-junosheskom sporte, stanovlenie masterstva odarennyh sportsmenov v legkoj atletike - Kozlov, K. (Science in Olympic Sport, 2018)
Objective. Improvement of the process of multi-year training on the basis of studying competitions in children`s and youth sports and development of skills in gifted athletes in track and field athletics. Methods. Theoretical analysis and generalization of scientific and methodological literature and information on the Internet, legislative acts and normative documents of the International Association of Athletics Federations, data from the information database of track and field athletics, published and electronic sources of the Association of Statisticians in Track and Field Athletics, IAAF electronic resources, statistical databases, methods of mathematical statistics. Results. Competitions in children's and youth sports (through the example of track and field athletics) were analyzed. The current state of the existing competition system and discussions related to their holding were reviewed. Sporting experience of recent years has shown that athletes, who have achieved success in junior sport (n = 1332) and who have become medal winners of the Youth Olympic Games, in rare cases achieve success in high performance sport. Dropout of gifted athletes due to the transition from junior to senior level in sport is a serious problem of the modern system of training athletes. More than 95 % of athletes failed to achieve their performance results demonstrated in junior sport. One of the main reasons is forced training of young athletes. The studies showed the presence of a number of problems, especially regarding the position normative documents for children's and youth sports schools, specialized children's and youth sports schools, and schools of sports excellence. Conclusion. To further improve the system of multi-year training it is necessary to focus on the implementation of a qualitative approach that involves the compliance with the patterns and principles of consistent development of sports mastery for 8 to 12 years from the beginning of sports activity to the level of the highest achievements